If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -1(2k + 4) = 18 Reorder the terms: -6 + -1(4 + 2k) = 18 -6 + (4 * -1 + 2k * -1) = 18 -6 + (-4 + -2k) = 18 Combine like terms: -6 + -4 = -10 -10 + -2k = 18 Solving -10 + -2k = 18 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -2k = 18 + 10 Combine like terms: -10 + 10 = 0 0 + -2k = 18 + 10 -2k = 18 + 10 Combine like terms: 18 + 10 = 28 -2k = 28 Divide each side by '-2'. k = -14 Simplifying k = -14
| x^4-3x^3-8x^2+12x+16=0 | | -91-2x=-9x+56 | | 162=x+x+x | | x^2+4x+y^2+4y+8=0 | | x^2+20=12x-16 | | 6x-10=7x+10 | | threeconseutivenumbers=162 | | 2 | | 7a+7-6a=10 | | 4(4x-3)-6x | | 0=-4.9t^2+11t-27 | | 16y-13=18y-9 | | 13x+1=11x=9 | | px+py=zsolveforz | | 9+10=t | | 4y-6+4y-8 | | logx=0.82 | | 20y-16018y-9 | | 10x=y-9 | | X-2y=-19 | | 20y-14=18y-8 | | 12p96 | | x^2+5x+4 | | 4+5y+y-8 | | -3xx=5 | | 3x^5–7x^4+6x^2–14 | | -5+9n-6= | | 11w+21f+13w | | 23y-14=17y-8 | | n+4=-11 | | x^2+(x+15)^2=(2x-13)^2 | | -5n+9-6= |